2019
DOI: 10.1111/ajt.15123
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo perfusion induces a time- and perfusate-dependent molecular repair response in explanted porcine lungs

Abstract: Ex vivo lung perfusion (EVLP) shows promise in ameliorating pretransplant acute lung injury (ALI) and expanding the donor organ pool, but the mechanisms of ex vivo repair remain poorly understood. We aimed to assess the utility of gene expression for characterizing ALI during EVLP. One hundred sixty-nine porcine lung samples were collected in vivo (n = 25), after 0 (n = 11) and 12 (n = 11) hours of cold static preservation (CSP), and after 0 (n = 57), 6 (n = 8), and 12 (n = 57) hours of EVLP, utilizing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…In liver transplantation, microarray studies confirmed that liver biopsies with TCMR share very similar transcriptional phenotypes with those in renal allograft biopsies 12,13 . Transcriptional similarities are also present in heart and lung allograft biopsies 8‐11 . These publications show that groups of genes within certain molecular pathways are statistically significantly associated with specific Banff histological lesions, rejection phenotypes, and Banff diagnostic categories.…”
Section: Evolution Of Molecular Transplant Diagnosticsmentioning
confidence: 69%
See 2 more Smart Citations
“…In liver transplantation, microarray studies confirmed that liver biopsies with TCMR share very similar transcriptional phenotypes with those in renal allograft biopsies 12,13 . Transcriptional similarities are also present in heart and lung allograft biopsies 8‐11 . These publications show that groups of genes within certain molecular pathways are statistically significantly associated with specific Banff histological lesions, rejection phenotypes, and Banff diagnostic categories.…”
Section: Evolution Of Molecular Transplant Diagnosticsmentioning
confidence: 69%
“…Over the past 20 years, we estimate that more than 4000 organ transplant biopsies have been studied by whole transcriptome microarrays 2 . These have been conducted independently by several research groups, covering transplant biopsies of kidneys 3‐7 and, to a lesser extent, other organs 8‐13 . Different analytical approaches addressing relevant research questions from these data have been made available and reproduced by several research groups and transplant centers, covering a broad spectrum of phenotypes and patient demographics 14 .…”
Section: Evolution Of Molecular Transplant Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the anatomical and physiological similarities of pigs and humans, our large animal model is readily clinically translatable, and well-suited to the study of IRI and transplantation. In contrast to previous studies, 82,120 we assess the impact of NEVKP post-transplant, and examine the functional significance of ex-vivo observations. Our systems biology approach incorporates transcriptomic and targeted metabolomic analyses, as well as an analysis of upstream regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury-related gene expression was measured and peaking time with continual period analyzed. Six hours would be the utmost change in gene-level, which affects P/F ratio and interstitial inflammation [37]. Lungs recovered from uDCDDs were assessed by 4 h EVLP and CT scan.…”
Section: To Find Optimized Markers Of Quality Determinationmentioning
confidence: 99%